OUTCOME OF CEREBRAL CONTUSIONS DUE TO TRAUMATIC BRAIN INJURY - Zubair Ahmed Khan; Habib sultan; Amir Aziz; Shahrukh Rizvi; Tauqeer Ahmed; Waseem Ahmed (Journal of University Medical & Dental College, 2020)
ABSTRACT:BACKGROUND & OBJECTIVE: To compare the results of surgically operated vs conservatively treated patients of cerebral contusions due to traumatic brain injury.METHODOLOGY: This comparative study was conducted from January 2012 to December 2014 at the department of Neurosurgery, PGMI Lahore General Hospital, Lahore. A total of 50 patients were included in this study of both gender (male and female) and in the age range of 15-65 years. In our study 20 patients were managed conservatively while other 30 patients were operated for cerebral contusions. The mode of injury in our study was road traﬃc accidents and history of falls.RESULTS: Out of 50 patients, there were 41 (82%) males and 09 (18%) female patients. Their age ranged from 15 - 65 years. In this study the overall mean age is 38.36 years. The maximum numbers of patients were in their third and fourth decades of life. In our study the duration of hospital stay in conservatively managed patients was longer as compared to surgically treated patients who were discharged earlier. Mortality rate in surgically managed patients having a GCS ranged between 09 to 12 was very low contrary to the conservatively managed group, similarly the rate of delayed contusion formation and edema was also low in surgically managed patients as compared to those who were managed conservatively.CONCLUSION: Surgically managed patients of cerebral contusions in traumatic brain injury has better outcome and decreased hospital stay as compared to conservatively managed patients.